Analysis of Artificial Intelligence (AI) Implementation in Language Skill Learning for Elementary School Students - Ari Susandi; Ali Firdaus Ibadulloh; Andys Nur A’Zunna Alita; Friski Adelia Fitri Ayu; Ahmad Ipmawan Kharisma; Rizka Novi Irmaningrum; Humairah Humairah; Oriza Zativalen (Universitas Muhammadiyah Lamongan, 2026)
The rapid expansion of Artificial Intelligence (AI) The Industrial Revolution 4.0 in education represents a response to the need to transform the relationship between humans and technology, thereby unlocking new opportunities through creativity and innovation. During this transitional period, teachers must provide support. Following the Industrial Revolution 4.0, we are now entering the Society 5.0 era; consequently, cutting-edge innovation is required to address the challenges of this new era Society 5.0 is envisioned as a state in which humans are at the center of society, resolving various life challenges by making balanced use of Industry 4.0 technologies. Its primary goal is the equitable distribution of prosperity The entire population can experience the benefits of development through the application of technologies such as Artificial Intelligence, IoT, big data, and robotics in areas ranging from transportation and logistics for remote regions to healthcare, education, and other essential public services. Therefore, we must prepare ourselves and enhance the quality of our human resources to ensure we can adapt to and utilize these technologies effectively and appropriately. Over the past few decades, digital technologies specifically Virtual Reality (VR), Augmented Reality (AR), and Artificial Intelligence (AI) have increasingly been integrated into education This study employs a contextual descriptive-qualitative approach aimed at understanding the implementation of Artificial Intelligence (AI) in the language skills of elementary school students. The aim of this study is to analyze the implementation of Artificial Intelligence (AI) in language skills learning for elementary school students. A case study approach utilizing a review of existing research articles was selected because the researcher sought to gather in-depth data from diverse sources. Descriptive qualitative approaches offer broad insights into specific phenomena and serve various functions in educational research, including as standalone designs, preliminary qualitative studies for larger projects, or qualitative components within mixed-methods studies.